An experimental investigation of satisfaction and commitment in marketing channels: the role of trust and dependence - Andaleeb, Syed Saad (© 1996 Published by Elsevier Inc., 2016)
This article was published in the Journal of Retailing [©1996 Published by Elsevier Inc.] and the definite version is available at: http://doi.org/10.1016/S0022-4359(96)90006-8 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0022435996900068